2021
DOI: 10.1002/jcop.22563
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19‐related psychiatric impact on Italian adolescent population: A cross‐sectional cohort study

Abstract: We investigated the prevalence rate and sociodemographic correlates of COVID-19-related posttraumatic stress disorder (PTSD), and COVID-19-related acute stress disorder (ASD) among Italian adolescents, their level of stress, perception of parental stress, and connection with mental health. Adolescents aged 12-18 years compiled an online questionnaire designed through validated diagnostic instruments. We enrolled 1262 adolescents who declared that they had not experienced any previous traumatic events. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Therefore, lockdown has had a negative psychological impact on the emotional wellbeing of this population, increasing the already high rate of mental health problems reported before the pandemic (Sadler et al, 2021). A recent systematic review assessed the impact of the pandemic on the mental health of adolescents around the world, showing that adolescents present higher rates of anxiety, depression, and stress (Jones et al, 2021), particularly those with psychiatric or psychological conditions (Mensi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lockdown has had a negative psychological impact on the emotional wellbeing of this population, increasing the already high rate of mental health problems reported before the pandemic (Sadler et al, 2021). A recent systematic review assessed the impact of the pandemic on the mental health of adolescents around the world, showing that adolescents present higher rates of anxiety, depression, and stress (Jones et al, 2021), particularly those with psychiatric or psychological conditions (Mensi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A study was found that adolescents with subthreshold psychiatric/psychological problems and COVID‐19‐related acute stress disorder and posttraumatic stress disorder symptoms reported the highest levels of personal stress, while adolescents with psychiatric/psychological disorders reported the greatest levels of stress. Prioritizing psychosocial stresses among the adolescent population should be a top priority for health efforts (Mensi et al, 2021 ). Individuals who fully complied with COVID‐19 measures had higher phobia scores associated with COVID‐19 as expected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 132 screened full texts, 82 studies were excluded because their topic did not meet our inclusion criteria, and 30 studies were excluded because insufficient data were available to include them in the systematic review. In the end, 18 studies (15 written in English and 3 written in Chinese) were included in our systematic review [10][11][12][13][14][15][20][21][22][23][24][25][26][27][28][29][30][31], of which 10 studies were included in our meta-analysis [11,12,14,15,[23][24][25][26][27]29]. The remaining eight studies could only be included in our systematic review because insufficient data were available for the meta-analysis.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Therefore, we describe discuss these risk factors of child PTSD in a systematic review. We classified each risk factor into one of four categories: (a) personal and family characteristics, (b) infectious diseases related factors, (c) internal and external support system ('external system' refers to support from outside the individual [e.g., government], while 'internal system' refers to supporting individual perspective [e.g., resilience]), and (d) psychological and behavioral changes [10][11][12][13][14][15][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Potential Influential Factors For Post-pandemic Child Ptsdmentioning
confidence: 99%